The Crisis Management Experiences of Female Media Leaders During The Pandemic - Amida Yusriana; Sunarto Sunarto; Nurul Hasfi (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2021)
The Covid-19 pandemic entered Indonesia in February 2020, one month later most of the institutions changed their work policies. Business processes have also changed. Leaders at all levels are tested to be adaptive to unpredictable conditions, including the media business which is also affected by the effects of the pandemic. The leaders of female countries have shown good performance, as evidenced by the number of countries they lead that have succeeded in reducing the number of Covid-19 transmissions. Women leaders are considered to be more responsive and quick. Even so, how the experiences of women leaders at other leadership levels have not been well covered in any media. So this study will try to understand the experiences of female media leaders during the pandemic in 2020 as well as the initial steps for crisis management. This study uses a critical paradigm with a descriptive approach. The theory used is Standpoint Theory developed by Sandra Harding and Julia T. Wood and Crisis Management. This theory seeks to understand the world through women's eyes. The method used is critical phenomenology. The results showed that women as media leaders act quickly, utilize technology, and adapt business processes. Apart from that, it puts forward four crisis management steps in its implementation.